Community Empowerment dan Sosialisasi Bahaya Covid-19 di Dusun Karpote Desa Larangan Slampar - Sukron Ma'mun; Abubakar Basyarahil; Abdurahman Abdurahman; Heru Wahyudi; Anggi Palupi (Jurnal Pemberdayaan Umat, 2023)
Purpose: This service has four five, namely, first, increasing community empowerment in the economic, agricultural, livestock, education, and health sectors. Second, increasing the empathy and concern of the activity implementation team to the community through Village Abdi and Social Work activities. Third, instill responsibility, independence, perseverance, leadership, and entrepreneurship in the implementation team through Village Abdi and Social Work activities. The fourth teaches the implementation team to be able to work together in a group through Village Abdi and Social Work activities. The fifth positively contributes to the development of information, knowledge, and economy of the people of Dusun Karpote, Larangan Slampar. Methodology: This research method is socialization given by the Village Abdi activities and Social Work implementation team to the people of Karpote Hamlet, Larangan Slampar Kecamatan Tlanakan, and Pameka Regency. Results: The results of community service produce the output of public awareness to maintain environmental cleanliness. Second, to raise public awareness related to the dangers of Covid-19 and the importance of wearing masks during the Covid-19 pandemic. Third, with this activity, the community, especially school children. Fourth, farmers can make Bokashi so that manure waste can be processed optimally. Fifth, the community is helped by a cheap market and distributing necessities to the poor—Sixth, fostering public awareness regarding a sustainable economy through planting betel nut seedlings. Limitations: This service activity was carried out during the Covid-19 pandemic, so it has several limitations. Namely, implementing activities must pay attention to health protocols, including ensuring the number of participants is manageable. Contribution: This research contributes to helping the community raise cleanliness awareness, adds to the community's economy, and provides knowledge about sustainable development.